THE REPRESENTATION OF UNCLAIMED EXPERIENCE IN MURATA'S EARTHLINGS - Hilwa Izmi Rumatiga; Ahmad Ghozi (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This article explores the representation of trauma in Sayaka Murata's novel Earthlings through its protagonist, Natsuki, who experiences sexual abuse and domestic violence from childhood. This research aims to analyze how hidden traumatic experiences are represented within Cathy Caruth's framework of Unclaimed Experience. This research uses literary criticism methods to explain the trauma in the novel. The results show that Natsuki's trauma manifests in five main forms: dissociation, emotional numbness, sensory disturbances, unspeakability, and cognitive confusion. These findings indicate that traumatic experiences never fully claimed by consciousness continue to resurface in fragmented and unconscious ways, shaping the protagonist's inner world throughout the narrative.